2013
DOI: 10.13169/worlrevipoliecon.4.1.0086
|View full text |Cite
|
Sign up to set email alerts
|

The Long Roots of the Present Crisis: Keynesians, Austerians, and Marx's Law

Abstract: The ultimate cause of crises in capitalism is lack of profitability. The Keynesian and Austerians (the supporters of austerity measures), deny this. So their solutions to crises do not work. Keynesian state-induced stimulus programs (redistributive, monetary, and fiscal) cannot overcome the underlying tendency for profitability to fall. The same holds for the policies of "austerity," which are designed to reduce debt and raise profitability. These conclusions are particularly relevant for the weaker Eurozone e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This group includes the works of Carchedi & Roberts (2013), Itoh (2012) and Herrera & Andreani (2015). The first two articles engage in a debate against Keynesianism, as a practice of economic policy, while the third article critically dialogues against the well-known book "Capital in the 21st century", by Thomas Piketty.…”
Section: The Theoretical Debatementioning
confidence: 99%
“…This group includes the works of Carchedi & Roberts (2013), Itoh (2012) and Herrera & Andreani (2015). The first two articles engage in a debate against Keynesianism, as a practice of economic policy, while the third article critically dialogues against the well-known book "Capital in the 21st century", by Thomas Piketty.…”
Section: The Theoretical Debatementioning
confidence: 99%
“…On the other hand, John Maynard Keynes, a renowned economist of the early 20th century, revolutionized macroeconomic theory with his emphasis on government intervention through fiscal policies during times of economic downturn (Skousen, 2015). Keynes argued that during recessions or depressions, market forces alone might not be sufficient to restore economic equilibrium (Carchedi & Roberts, 2013). He advocated for increased government spending and tax cuts to stimulate aggregate demand and counteract the negative effects of a downturn (Makin & Layton, 2021).…”
Section: Zainal Arifin Mustofa Aji Prayitno Eko Sudarmantomentioning
confidence: 99%
“…For, as profits rise in the numerator so they rise in the denominator to the same amount but in the opposite direction. By including profits or interest in both the numerator and the denominator of the rate of profit calculation, so an increase in profits is measured as a fall of it, as in Roberts and Carchedi (2018) and Tsoulfidis and Tsaliki (2019).…”
Section: The Fixed Capital Stock and Their Neoclassical Valuationmentioning
confidence: 99%
“…Michael Roberts and Guglielmo Carchedi (2018) observed that their estimates of 'constant capital includes only fixed and not circulating capital because of difficulties of estimating the latter on the basis of the available statistics' (p. 31). Roberts and Carchedi (2018) did not deflate variable capital by turnover and so conflated the rate of S/V and the annual rate of S/V (pp. 13-39).…”
Section: Circulation Time and The Rate Of Profit Discussedmentioning
confidence: 99%